Continuity or rupture? : the shaping of the rural political order through contestations of land, community, and mining in the Bapo ba Mogale traditional authority area - Malindi, Stanley (My University, 2016)
South Africa’s countryside’s are rich in ‘new’ high-demand metal and energy minerals, like platinum and uranium, as well as vast, untapped reserves of industrial staples, above all coal. Yet, these are also characterised by deep rural poverty and legally insecure systems of ‘customary’ tenure, under the local administrative control of traditional authorities. Here, new mining activity is setting in motion significant processes dispossession and Immiseration that are at once tracing, reconfiguring and widening the class, gender and other social divisions that define these rural settings. Communal land is frequently alienated with little or no compensation, local residents forcibly removed to make way for surface infrastructure, and scarce water and other natural resources polluted and depleted. At the same time political tensions are arising from the assumption that local chiefs are ‘custodians’ of the mineral-rich land under their jurisdiction. Questions of land, livelihood and rural democracy are thus intimately bound together on the new frontiers of the regional extractives boom in ways that are having profound implications for growing numbers of the rural poor. Using a case study of the Bapo ba Mogale traditional Authority in the North West Province, South Africa, this thesis seeks to explore how these new mining activities are shaping and reconfiguring the heightened political contestations over the institution of traditional leadership in the area, the definitions of community and belonging/exclusion, and the struggles over land ownership and how mining capital is shaping these struggles and is connected with these struggles
A research project submitted at the University of the Witwatersrand, Department of Political Studies, School of Social Sciences, in fulfilment of the Master of Arts (Research) Degree.
Keywords: Tribal government--South Africa; North-West (South Africa)--Social conditions; South Africa--Politics and government